2020
DOI: 10.1007/s10888-020-09445-8
|View full text |Cite
|
Sign up to set email alerts
|

Tax progressivity and top incomes evidence from tax reforms

Abstract: We study the link between tax progressivity and top income shares. Using variation from large-scale Western tax reforms in the 1980s and 1990s and the novel synthetic control method, we find large and lasting boosting impacts on top income shares from the progressivity reductions. Effects are largest in the very top groups while earners in the bottom half of the top decile were almost unaffected by the reforms. Cuts in top marginal tax rates account for most of this outcome whereas reduced overall progressivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…Our results on changes in top income compensation are consistent with these results. They are also consistent with Rubolino and Waldenström (2018a), who find evidence at the country level that reductions in personal income tax progressivity increases income for top earners. In addition, our findings are related to a large literature that documents that top earners are more sensitive to taxation than other tax payers (Feenberg and Poterba, 1993;Feldstein, 1999;Slemrod, 1996;Gruber and Saez, 2002;Saez, 2004;Saez, Slemrod and Giertz, 2012;Piketty, Saez and Stantcheva, 2011;Rubolino and Waldenström, 2018b,a;Saez, 2017).…”
supporting
confidence: 89%
“…Our results on changes in top income compensation are consistent with these results. They are also consistent with Rubolino and Waldenström (2018a), who find evidence at the country level that reductions in personal income tax progressivity increases income for top earners. In addition, our findings are related to a large literature that documents that top earners are more sensitive to taxation than other tax payers (Feenberg and Poterba, 1993;Feldstein, 1999;Slemrod, 1996;Gruber and Saez, 2002;Saez, 2004;Saez, Slemrod and Giertz, 2012;Piketty, Saez and Stantcheva, 2011;Rubolino and Waldenström, 2018b,a;Saez, 2017).…”
supporting
confidence: 89%
“…This question addresses key aspects of tax system design because top income earners usually pay a disproportionate share of all income taxes. At the same time, top earners have been found to be more sensitive to taxation than most other taxpayers in the population (see, e.g., Feenberg and Poterba, 1993;Feldstein, 1995;Slemrod, 1996;Gruber and Saez, 2002;Saez, 2004;Saez, Slemrod and Giertz, 2012;Rubolino and Waldenström, 2017;Saez, 2017). While there is relatively scarce evidence on this matter, several explanations have been proposed for the higher tax elasticities among top earners, some emphasizing the role of real, laborsupply related responses (e.g., Feldstein, 1995) while others highlight the role of tax avoidance activities (e.g., Auerbach, 1988;Slemrod, 1995;Goolsbee, 2000;Saez, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The question of whether an enterprise´s ability to pay tax is affected by the amount of corporate income was addressed by a hypothesis claiming that tax burden is more demanding with a higher income. The authors concluded that tax burden is more burdensome for an enterprise or entrepreneur with a higher income; the hypothesis was thus confirmed [10]. In Germany, research was conducted to examine the relationship between tax burden and income, more specifically, the adequacy of the tax system.…”
Section: Introductionmentioning
confidence: 93%